THE INFLUENCE OF ECONOMIC PARAMETERS ON THE LEVEL OF LIGHT POLLUTION - CAUSES, CONSEQUENCES AND SOLUTIONS FOR THE IMPROVEMENT OF THE ENVIRONMENT - Majhenšek, Katarina R; Josimović, Boško; Manić, Božidar (Arhitektura i urbanizam, 2017)
The purpose of this paper is to raise the awareness of the importance of light pollution as an essential, but neglected factor that impacts the living and the built environment. One of the main causes of light pollution is the continual economic growth of the cities. Two studies have been presented with an aim of clarifying the attempts made so far in establishing the way population growth and living standards affect light pollution. The unique contribution of this paper is that the correlation between the economical parameters that imply a certain living standard of a country to the level of its light pollution is analysed using the Pearson Correlation Coefficient. For the first time a very accurate VIIRS (Visible Infrared Imaging Radiometer Suite) is used for the measurements of light radiation in order to determine such a correlation. The analysis takes into account the African continent as one of the poorest parts of the world, and Europe, as one of the richest continents. The consequences of light pollution and some ways of reducing and minimizing it have been explained through case studies. The paper highlights the need for change in local authorities' approach to solving the problem of light pollution, raising citizens’ awareness of the issue, as well as proposing zoning parameters in lighting design of public spaces. Key words: light pollution, economic development, Pearson Correlation Coefficient, urban planning of the cities, zoning and lighting design of public areas